PENGARUH PEMBELAJARAN KOOPERATIF GROUP TO GROUP EXCHANGE DAN LKPD TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Enie Augus Junaety (Epsilon: Jurnal Pendidikan Matematika, 2019)
This study aims to determine the effect of cooperative learning group to group exchange and LKPD on mathematical communication skills. The study was conducted in the first semester of the academic year 2019/2020 at SMAN 2 Metro. The population in this study is the students grade XI IPA at SMAN 2 Metro in the academic year 2019/2020. Data were collected using two classes derived from the experimental class and control class. Samples were selected through purposive random sampling technique. The study design is a post-test only design. Based on the results of research and discussion can be concluded that there are significant cooperative learning group to group exchange and LKPD on mathematical communication skills among students of class XI IPA in the first semester of SMAN 2 Metro.